Effect of host genetics and gut microbiome on fat deposition traits in pigs - Wang, Yuan; Zhou, Ping; Zhou, Xiang; Fu, Ming; Wang, Tengfei; Liu, Zuhong; Liu, Xiaolei; Wang, Zhiquan; Liu, Bang (Frontiers in Microbiology, 2022)
Fat deposition affects meat quality, flavor, and production in pigs. Fat deposition is influenced by both genetics and environment. Symbiotic microbe with the host is an important environmental factor to influence fat deposition. In this study, the fat deposition traits were measured in 239 individuals obtained from Tongcheng pigs × Large White pigs resource pig population. The interactions between genetics and gut microbiome in fat deposition traits was investigated through whole-genome sequencing and cecum microbial 16S ribosomal RNA sequencing. The results showed that the percentage of leaf fat (PL) and intramuscular fat content (IMF) were significantly influenced by host genetics-gut microbiome interaction. The effects of interactions between host genetics and gut microbiome on PL and IMF were 0.13 and 0.29, respectively. The heritability of PL and IMF were estimated as 0.71 and 0.89, respectively. The microbiability of PL and IMF were 0.20 and 0.26, respectively. Microbiome-wide association analysis (MWAS) revealed Anaeroplasma, Paraprevotella, Pasteurella, and Streptococcus were significantly associated with PL, and Sharpea and Helicobacter exhibited significant (p < 0.05) association with IMF. Furthermore, Paraprevotella was also identified as a critical microbe affecting PL based on the divergent Wilcoxon rank-sum test. Overall, this study reveals the effect of host genetics and gut microbiome on pig fat deposition traits and provides a new perspective on the genetic improvement of pig fat deposition traits.